2007
DOI: 10.2310/7750.2007.00037
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Comprehensive Acne Severity Scale

Abstract: Concurrent validity of CASS is demonstrated by a very strong correlation with Leeds grading. CASS is simpler to use than the Leeds system and more appropriate for translation of research trial results to clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 12 publications
0
102
0
3
Order By: Relevance
“…Subsequent analysis has shown that the facial component of the scale is skewed to higher grades of facial acne severity with inadequate representation of milder forms. 17 Thus these scales did not adequately fulfill the required elements for clinical components and/or features identified in this study. In a recent review of measurement properties of investigator-assessed outcome measures for acne, 9 separate assessment methods were identified.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequent analysis has shown that the facial component of the scale is skewed to higher grades of facial acne severity with inadequate representation of milder forms. 17 Thus these scales did not adequately fulfill the required elements for clinical components and/or features identified in this study. In a recent review of measurement properties of investigator-assessed outcome measures for acne, 9 separate assessment methods were identified.…”
Section: Discussionmentioning
confidence: 95%
“…This scale comprises 6 categories and is based on a global assessment previously used in clinical trials. 17 However, this scale combines noninflammatory and inflammatory lesions into aggregate categories. The Global Acne Grading system (GAGS), a quasiquantitative scheme combining regional evaluation of 6 sites (5 facial and 1 truncal) with scores for lesion type and number summed to provide an overall global score, has been proposed but has not yet been validated.…”
Section: Discussionmentioning
confidence: 99%
“…3 The frequency distribution of acne in this population using this system has previously been published. 5 An overall acne severity score was obtained by summation of acne grades from each of the face, chest, and back.…”
Section: Methodsmentioning
confidence: 99%
“…All these scoring systems focus only on the lesions of facial acne and therefore do not take into account other factors tbat may influence the severity of acne. Very recently Tan et al (10) proposed a new severity scale for facial and truncal acne. In clinical practice, therapeutic decisions are based on a global assessment of severity, taking into account not only the number of lesions, their type and their extension on the face, but also other sites of involvement and the patient's history, including responses to prior treatments.…”
mentioning
confidence: 99%